Leader evolution : from technical expertise to strategic leadership - Patterson, Alan. (2014 digital library., 2015)
Most individuals who move into leadership positions experience the modern day version of trial by ordeal. It's sink or swim. To reduce the learning curve and create a more effective process, Leader Evolution describes a road map for leadership development, a series of four stages that expand personal competence as well as create a broader impact on the organization or business. Each stage requires unique changes in thinking, perspective taking, and behavior, both those needed to acquire as well as those needed to jettison. The book is a pragmatic approach for self-motived individuals to take control of their professional development by giving them the concepts, tools, techniques, and assignments to develop their leadership effectiveness where it counts the most--on the job. In addition to new and existing managers, the book is ideally suited for technical professionals and leaders in technical organizations looking to develop critical leadership behaviors distinct from technical expertise. These include individuals who are moving on a technical rather than managerial track. The broad application of concepts and techniques also makes this book appealing to organizations developing their leaders as part of broad change initiatives. While the concepts and principles are directed toward the individual for on-the-job application, the book serves as an organizational and leadership development resource for Executive MBA programs as well as a blueprint for in-house leadership development programs.